Effect of Work Motivation and Compensation on Employee Performance at PT.Askrindo (Persero) Cikini Central Jakarta - Faif Yusuf; Marlina Rahmi Shinta; Sonny Fransisco (Journal of Research in Business, Economics, and Education, 2020)
This study aims to determine: (1) The effect of motivation on employee performance at PT. Askrindo (Persero) Cikini, Central Jakarta. (2) The Effect of Compensation on Employee Performance at PT. Askrindo (Persero) Cikini Central Jakarta. (3) The Effect of Motivation and Compensation on Employee Performance at PT. Askrindo (Persero) Cikini Central Jakarta. This study uses a quantitative approach. This study collected primary data with a questionnaire. The questionnaire distributed is a list of written statements regarding Motivation and Compensation for Employee Performance at PT. Askrindo (Persero) Cikini Central Jakarta. To analyze the independent variable on the dependent variable, multiple linear regression analysis was performed using the help of a computer program, namely SPSS Statistics. The results showed that there was a positive and partially significant influence on Motivation with Employee Performance Performance at PT. Askrindo (Persero) Cikini Central Jakarta. A simultaneously positive and significant influence on Motivation and Compensation with Employee Performance at PT. Askrindo (Persero) Cikini Central Jakarta.